Ant colony optimisation for the routing problem in the constellation network with node satellite constraint. (2017) - Li, Jing; Ke, Liangjun; Ye, Gangqiang; Zhang, Tianjiao
In the field of satellite communication, there is a trend towards interconnecting satellites into a heterogeneous network. Inter-satellite links (ISLs) are used to transmit satellite management data, such as telemetry and telecommand data, as well as application data. The ground stations act as a management entity, which are connected with node satellites. This paper considers a routing problem with the aim of combining the satellite network with ground station management network to make integrated planning under the node satellite constraint. Based on the characteristic of the routing problem, ant colony optimisation is adopted to solve it. Two solution construction methods, i.e., the sequential method and concurrent method, are proposed. Experimental results on real data show that the concurrent ACO algorithm is better, and it can provide better data transmitting bandwidth of ISLs and save ground station management resources, which makes the algorithm suitable for real requirements.